Delayed-Onset Seizure in a Mild Quetiapine Overdose: Report of a Case and Review of the Literature - Jason A. Chen; Katherine M. Unverferth; Erick H. Cheung (Case Reports in Psychiatry)
Among atypical antipsychotics, quetiapine is commonly prescribed and considered to have a favorable side effect and safety profile. Here, we report the case of a patient who developed a generalized tonic-clonic seizure 28 hours following ingestion of 1,400 mg of quetiapine. Review of the literature identifies delayed-onset seizure as a potential complication of quetiapine overdose. Unique to this case, delayed-onset seizures occurred in a patient with a relatively low dose of quetiapine and no obvious toxidrome, suggesting that this reaction may be an important consideration in the management of quetiapine overdose. The pharmacokinetics and pharmacodynamics of quetiapine may explain this unusual phenomenon.